Rapid sequential clustering of NMDARs, CaMKII, and AMPARs upon activation of NMDARs at developing synapses - Chen, Yucui; Liu, Shangming; Jacobi, Ariel A.; Jeng, Grace; Ulrich, Jason D.; Stein, Ivar S.; Patriarchi, Tommaso; Hell, Johannes W. (Frontiers in Synaptic Neuroscience, 2024)
Rapid, synapse-specific neurotransmission requires the precise alignment of presynaptic neurotransmitter release and postsynaptic receptors. How postsynaptic glutamate receptor accumulation is induced during maturation is not well understood. We find that in cultures of dissociated hippocampal neurons at 11 days in vitro (DIV) numerous synaptic contacts already exhibit pronounced accumulations of the pre-and postsynaptic markers synaptotagmin, synaptophysin, synapsin, bassoon, VGluT1, PSD-95, and Shank. The presence of an initial set of AMPARs and NMDARs is indicated by miniature excitatory postsynaptic currents (mEPSCs).However, AMPAR and NMDAR immunostainings reveal rather smooth distributions throughout dendrites and synaptic enrichment is not obvious. We found that brief periods of Ca 2+ influx through NMDARs induced a surprisingly rapid accumulation of NMDARs within 1 minute, followed by accumulation of CaMKII and then AMPARs within 2-5 minutes. Postsynaptic clustering of NMDARs and AMPARs was paralleled by an increase in their mEPSC amplitudes.A peptide that blocked the interaction of NMDAR subunits with PSD-95 prevented the NMDAR clustering. NMDAR clustering persisted for 3 days indicating that brief periods of elevated glutamate fosters permanent accumulation of NMDARs at postsynaptic sites in maturing synapses. These data support the model that strong glutamatergic stimulation of immature glutamatergic synapses results in a fast and substantial increase in postsynaptic NMDAR content that required NMDAR binding to PSD-95 or its homologues and is followed by recruitment of CaMKII and subsequently AMPARs.